Kentucky Folk Architecture - Montell, William Lynwood, 1931- (Book collections on Project MUSE., 1995)
A concise and amply illustrated introduction to Kentucky folk structures--log cabins, houses, cribs, and barns--that should be treasured as irreplaceable expressions of the cultural values of the Commonwealth's past.